Vital Health Indicator Screening for Early Detection of Non-Communicable Diseases in Sigapiton Village, North Sumatra - Muh. Arfah; Cut Saura Salmira; Andi Muh Zulfikar; Nasrilia Rahmadina; Yuan Pariasi; Mahani Datita Sitepu; Teresia Talantan Kondolele (Universitas Ibn Khaldun, 2026)
Non-communicable diseases (NCDs) pose a growing global health burden, including in rural Indonesia. This community service program conducted vital health indicator screenings—covering blood pressure, blood glucose, uric acid, and total cholesterol—alongside structured health education on NCD prevention and control for residents of Sigapiton Village, Ajibata District, Toba Regency, North Sumatra. The program applied a community-based health screening approach with a quantitative descriptive design combined with a health education intervention. A total of 87 participants were enrolled (mean age 46.3 ± 12.7 years; 43.7% male, 56.3% female). Screening findings revealed hypertension in 34.5%, elevated blood glucose in 18.4%, hyperuricemia in 27.6%, and high total cholesterol in 31.0% of participants. Pre-post test evaluation demonstrated a mean knowledge score improvement of 27.5 points (from 52.3 ± 9.1 to 79.8 ± 7.4), with the greatest gains in knowledge of modifiable NCD risk factors (+35.2 points) and the benefits of routine health check-ups (+31.6 points). Notably, 72.4% of participants had never undergone any preventive health examination in the past year, underscoring the critical diagnostic gap in this rural setting. The high prevalence of hyperuricemia—exceeding the national average—reflects local dietary patterns rich in high-purine foods common in the Lake Toba region. Community-based health screening combined with contextual health education proved effective as an early detection and prevention strategy for NCDs at the village level. Routine integration of such programs into the existing primary health care system is recommended.